ByzRev 07.2025.031: Liv Ingeborg Lied – Brent Nongbri, Working with Manuscripts:: A Guide for Textual Scholars. New Haven: Yale University Press 2025. - Montoro IV, Peter J. (The Byzantine Review, 2025)
Liv Ingeborg Lied – Brent Nongbri, Working with Manuscripts: A Guide for Textual Scholars. New Haven: Yale University Press 2025. viii+179 pp. – ISBN 978-0-300-26442-5